Comparative Study of the Time Variable Between Grab Start and Track Start Types in Freestyle Swimming for Elite Swimmers - Qusay Abdul Latif, Waleed (Journal of Physical Education, 2026)
Research aims to identify the time variable values between the two types of start: the Grab start and the track start in advanced freestyle swimming, and see the difference of the time variable between the two types of start: the Grab start and the track start in advanced freestyle swimming.To achieve the research objective, the researcher used a descriptive method using a comparative approach, as it was best suited to the research problem. The research sample was selected purposively, consisting of four (4) advanced swimmers from the national 100m freestyle team, representing 80% of the original research population of five (5) swimmers, due to injury, one of swimmer was excluded. The researchers conducted the test with video recording, and performed kinematic analysis of the swimmers using the Kinovea analysis software to extract the biomechanical variables related to start time. Appropriate statistical analyses were performed, and the researcher concluded that the swimmers achieved a shorter start time in the Grab start compared to starting from the track start, indicating its better in improving the overall performance time of the freestyle swim. The Grab start contributed to reducing the time of the start and entering the water more efficiently, due to faster reaction times and more efficient distribution of kinetic energy. Furthermore, the type of start used had a clear impact on gaining initial speed, which positively affected maintaining movement rhythm during the first meters of the swim race.The researcher recommends using the Grab start as a basically method in training and competitions in freestyle swimming for the advanced category, due to its superiority in reducing the time variable and improving the achievement, and the necessity of including special training for the start phase within the daily training units, with a focus on developing reaction speed and explosive power of the legs, also the necessity of using video recording and motion analysis to evaluate the swimmers’ performance in the start phase and correct technical errors.